Regulatory effect of inflammatory mediators in spinal cord injury - Zeng, Wen-cong; Zeng, Fang-jun (Frontiers in Immunology, 2025)
Spinal cord injury (SCI) is a severe disabling central nervous system injury that can lead to severe sensory and motor dysfunction, and even paralysis. Depending on the mechanism of injury, SCI can be divided into primary injury and secondary injury. While secondary injury is the most critical stage in the pathophysiological process of SCI, which is the uncontrolled destructive cascade that follows. At present, symptoms are mainly alleviated and endogenous repair mechanisms are improved through drug intervention, surgical decompression and rehabilitation therapy, but they cannot directly promote nerve regeneration and functional recovery. Recently, an increasing number of studies have shown that the inflammatory response is a core link in secondary injury and plays a crucial role in regulating the pathological progression of acute and chronic SCI. Inflammatory mediators are key participants in the inflammatory response, which can trigger various neuropathological conditions and neurological dysfunction and are related to the severity of the injury. They are being explored as potential therapeutic targets for SCI and related diseases. Therefore, reducing the production of pro-inflammatory mediators is feasible and will also become a research hotspot in the future. This article summarizes the main sources of inflammatory mediators related to injury, their expression regulation, the key signaling pathways that regulate their production (such as Toll-like receptors, NF-κB, MAPK pathways, etc.), and their impact on the pathophysiology of SCI. In addition, treatment methods such as chemical antagonists, plant extracts and hormone therapy have been introduced to inhibit the expression of inflammatory mediators in order to control and improve the inflammatory microenvironment. This article mainly relies on preclinical research evidence to deeply analyze the core position of inflammatory mediators, providing a theoretical basis and direction guidance for the development of more effective SCI anti-inflammatory treatments.